2D Janus Hybrid Materials of Polymer‐Grafted Carbon Nanotube/Graphene Oxide Thin Film as Flexible, Miniature Electric Carpet. (27th February 2015) - Xiao, Peng; Wan, Changjin; Gu, Jincui; Liu, Zhenzhong; Men, Yonghong; Huang, Youju; Zhang, Jiawei; Zhu, Liqiang; Chen, Tao
Abstract : Ultrathin, freestanding polymer hybrid film with macroscopic sizes and molecular thicknesses have received significant interest due to their applications as functional devices, microsensors or nanoactuators. Herein, a 2D Janus hybrid of polymer‐grafted carbon nanotubes/graphene oxide (CNTs/GO) thin film is fabricated using microcontact printed CNTs/GO as photo active surface to grow polymer brushes by self‐initiated photografting and photopolymerization selectively from one side of CNTs/GO film. This achieved 2D Janus hybrid materials with grafted polymer layer as insulative carpet and supported CNTs/GO thin film as conductive element have the potential application as flexible and miniature electric carpet for heating micro‐/nano devices locally. Abstract : A polymeric electrical carpet of 2D Janus hybrid thin film, with grafted polymer layer as insulative carpet and supported carbon materials as conductive element, has the potential application in heating micro‐/nano devices locally.